2021
DOI: 10.3390/healthcare9060754
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative and Structured Network for Maintenance of Mechanical Ventilators during the SARS-CoV-2 Pandemic

Abstract: The SARS-CoV-2 pandemic in Brazil has grown rapidly since the first case was reported on 26 February 2020. As the pandemic has spread, the low availability of medical equipment has increased, especially mechanical ventilators. The Brazilian Unified Health System (SUS) claimed to have only 40,508 mechanical ventilators, which would be insufficient to support the Brazilian population at the pandemic peak. This lack of ventilators, especially in public hospitals, required quick, assertive, and effective actions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It determined the key reason for the reduction in the rate of the OEE due to losses as a result of (76.29%) machine failure, (9.59%) setup time, (8.80%) idle time, and minor stop, and (5.29%) decrease in speed [2]. Nevertheless, in the context of maintenance policies used for ventilator devices identified the operational issues, inspection, cleaning, providing supper parts, replacing, repairing, and calibrating the ventilators to meet operational parameters [4]. OEE can be calculated using the following equations [18]:…”
Section: Overall Equipment Effectiveness (Oee)mentioning
confidence: 99%
See 4 more Smart Citations
“…It determined the key reason for the reduction in the rate of the OEE due to losses as a result of (76.29%) machine failure, (9.59%) setup time, (8.80%) idle time, and minor stop, and (5.29%) decrease in speed [2]. Nevertheless, in the context of maintenance policies used for ventilator devices identified the operational issues, inspection, cleaning, providing supper parts, replacing, repairing, and calibrating the ventilators to meet operational parameters [4]. OEE can be calculated using the following equations [18]:…”
Section: Overall Equipment Effectiveness (Oee)mentioning
confidence: 99%
“…Then reducing treatment time and total maintenance costs [21]. A study by Motta et al (2021) indicated the adoption of a successful maintenance program that contributed to the available around (62.17%) of the ventilator machine during the Corona pandemic crisis in Brazilian [4].…”
Section: Reliability-centred Maintenance (Rcm)mentioning
confidence: 99%
See 3 more Smart Citations